Pengembangan Media Layanan Bimbingan Klasikal Berbasis TikTok tentang Pentingnya Self-Love dan Cara Menerapkannya dalam Diri Remaja - Shelly Maylinda; Hadi Pranoto; Eko Susanto (Universitas Muhammadiyah Metro, 2025)
The purpose of this research is to develop a TikTok-based classical guidance service media on the importance of self-love and how to apply it to adolescents. This research model is based on the development model by Dick and Carry (1996), with a modified development plan consisting of four stages: analysis, design, development, and implementation. Based on the research results, product development in the form of TikTok video content showed a positive response with feasibility results of